2010
DOI: 10.1111/j.1365-2753.2009.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of cost‐effectiveness, cost‐containment and economics curricula in graduate medical education

Abstract: Cost-effectiveness curricula in graduate medical education are lacking and clearly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 68 publications
0
37
0
Order By: Relevance
“…26 A more recent systematic review of health economics, cost-containment, and cost-effectiveness curricula in graduate medical education concluded that cost curricula in graduate medical education among internal and family medicine, surgical, pediatric, and emergency medicine residents are lacking. 27 Our study examines 1 subspecialty, PEM, and finds cost education in fellowship training still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…26 A more recent systematic review of health economics, cost-containment, and cost-effectiveness curricula in graduate medical education concluded that cost curricula in graduate medical education among internal and family medicine, surgical, pediatric, and emergency medicine residents are lacking. 27 Our study examines 1 subspecialty, PEM, and finds cost education in fellowship training still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The wide cost differences between QDU and hospitalized patients shown by our results (EUR 601.84 vs. 4,059.37) can be attributed mainly to staff costs, the hours worked, and the fixed costs of hospitalization (table 4), suggesting that diagnostic resources might be more effectively used by increasing QDU staff and, possibly, reducing internal medicine ward staff. In addition, studies have shown that care provided by medical residents may cost more than care not involving residents, with the difference sometimes being attributed to the resident’s lack of clinical judgment with respect to necessary and unnecessary procedures [35,36,37]. Ambulatory costs involving residents are almost double those attributed to attending specialists, mainly due to excessive diagnostic tests, especially magnetic resonance imaging and other radiology, more specialty consults per visit, twice as many hospitalizations, and more days of hospitalization [35].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of technology, high-fidelity simulators such as the Uro-Scopic Trainer and the ureteroscopy bench model from Limbs and Things have been utilized and are highly rated for the training of urology residents [16,17]. However, these models are costly [18] and many medical universities, including ours, are unable to afford them for undergraduate education, and therefore continue to use ordinary opaque plastic simulators. However, the opaque plastic simulator fails to provide a visual representation of the procedures internally, and some students are not able to form a clear idea of how the instruments work in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%